Microbial Derived Compounds Are a Promising Approach to Mitigating Salinity Stress in Agricultural Crops - Naamala, Judith; Smith, Donald L. (Frontiers in Microbiology, 2021)
The use of microbial derived compounds is a technological approach currently gaining popularity among researchers, with hopes of complementing, supplementing and addressing key issues associated with use of microbial cells for enhancing plant growth. The new technology is a promising approach to mitigating effects of salinity stress in agricultural crops, given that these compounds could be less prone to effects of salt stress, are required in small quantities and are easier to store and handle than microbial cells. Microorganism derived compounds such as thuricin17, lipochitooligosaccharides, phytohormones and volatile organic compounds have been reported to mitigate the effects of salt stress in agricultural crops such as soybean and wheat. This mini-review compiles current knowledge regarding the use of microbe derived compounds in mitigating salinity stress in crops, the mechanisms they employ as well as future prospects.